Invasive Streptococcus intermedius Infections in Children: Two Cases from a Pediatric Infectious Diseases Unit in Italy - Piero Veronese; Simone Cella; Alessandra Giacometti; Irene Lapetina; Valentina Maffini; Marco Pappalardo; Monica Rubini; Maria Beatrice Ruozi; Icilio Dodi (Pathogens)
In recent years, an increasing number of reports have described invasive infections caused by bacteria from Streptococcus anginosus group (SAGs). S. intermedius seems to be more related with pleuropulmonary infections and abscess of the brain and deep soft tissues, and it is more likely to cause suppurative and non-bacteremic infections compared to other members of the same genus. We present two clinical cases of invasive S. intermedius infections in pediatric patients: a liver abscess case and a pansinusitis case associated with bilateral otomastoiditis and parapharyngeal abscess complicated by acute mediastinitis, thrombophlebitis of the cavernous sinus, and thrombosis of the cranial tract of the ipsilateral jugular vein. In both cases, prompt broad-spectrum antibiotic therapy and operative drainage of the collections resulted in a good clinical response with full recovery.